Insights Into the Helical Shape Complex of Helicobacter pylori - Holtrup, Sven; Greger, Maximilian; Mayer, Benjamin; Specht, Mara; Waidner, Barbara (Frontiers in Microbiology, 2022)
One important factor promoting colonization of the upper digestive system of the human pathogen Helicobacter pylori is its helical cell shape. The bacteria cell shape is predominantly defined by its Peptidoglycan cell wall. In rod-shaped species, PG synthesis is mediated by two dynamic molecular machines which facilitate growth along the perpendicular axis and the septum, called the elongasome and the divisome, respectively. Further, many bacteria evolved additional mechanisms to locally change PG synthesis patterns to generate diverse cell shapes. Recent work characterizing cell shape mutants of Helicobacter pylori revealed a novel mechanism for the generation of a twisted helix from a rod, including PG-modifying enzymes as well as additional proteins like the bactofilin homolog CcmA or the membrane proteins Csd5 and Csd7. In this study, we investigate the localization and dynamics of CcmA and Csd7 using live-cell imaging. We also address the question of how these change in the presents or absence of the putative interaction partners.